Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Iphone Pada Masyarakat Kota Surakarta - Niken Vera Kusumawati; Saskia Anggun Choirunnisa; Rayhan Gunaningrat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This observation was made to determine the influence of product quality on the purchase decision of Iphone products among Surakarta residents. This observation used quantitative methods using manual data obtained by distributing documents or questionnaires and collecting responses from a sample of 59 participants. This observation uses Intelligent Partial Least Squares (PLS) analysis to evaluate the hypothesis, as well as using a quantitative approach. Based on the results of the Smart PLS analysis test conducted, it shows that product quality has a positive or significant effect on purchasing decisions.